DEGRADATION OF THE REFLECTANCE PROPERTIES OF SOME GSS IN SPACE, PRELIMINARY RESULTS - Sukhov, P. P.; Sukhov, K. P. (Одеські астрономічні публікації, 2020)
A spacecraft in near-Earth orbit is exposed to extreme environmental factors, such as high vacuum, zero gravity, collisions with meteors and orbital debris, corpuscular and electromagnetic radiations, etc. These factors result in changing properties of spacecraft surfaces which leads to changes in mechanical, optical, electrical and physical properties of materials and elements of spacecrafts. This paper presents experimental data obtained from ground-based photometric observations of several geostationary satellites (GSS) built on different types of buses, starting from the beginning of their operational lives and during several years after their launches. It has been experimentally proved that spectral reflectance properties of the satellite surface materials undergo gradual degradation with time of the satellite’s stay in space. Noticeable changes in spectral reflectance properties of GSS make it possible to detect damages to the satellite external payload. Comparison of changes in the reflective characteristics of different platforms over time can show the level of technical and scientific progress of spacecraft designers